Estimation of Time Duration for Using the Allocated LoRa Spreading Factor: A Game-Theory Approach - Kumari P.; Gupta H.P.; Dutta T. (My University, 2025)
Long Range (LoRa) is one of the most promising wireless communication technology because it allows for long-range communication with low power consumption. The interference problem in LoRa occurs when nodes are attached with a gateway using the same spreading factor. To overcome the problem, the literature assumes that the spreading factor is allocated to each node for a fixed time duration. Since all nodes may not have equal data to transmit to the gateway, the network revenue estimated by using fixed time duration is lower than the allocation based on the needs of the network. In this paper, we address the problem of estimating the time duration of using the allocated spreading factor for each node. Such time duration satisfies the service requirement of the node and maximizes the network revenue. We assume that each node in the network takes multiple services from the same or different gateways. We use the game theory approach for formulating the interaction among the nodes and interaction between gateways and nodes. We propose a solution that builds the strategic interactions among the gateways and nodes to estimate the time duration for using the allocated spreading factors. We also propose distributed and centralized algorithms for implementation of the solution. © 1967-2012 IEEE.